High pressure investigation of superconducting signatures in CeCu2Si2: ac-magnetic susceptibility, ac-heat capacity, resistivity and thermopower - Giriat, G. (2015)
Abstract Taking advantage of a novel multiprobe setup we have measured, on a unique sample, the ac-magnetic susceptibility, the resistivity, the ac-specific heat and the thermopower of the superconductor heavy fermion CeCu2Si2 under pressure up to 5.1 GPa. At the superconducting transition temperature Tc, the Meissner signal corresponds to that expected for the sample volume and coincides with the specific heat jump and the resistive transition completion temperatures. Differing from previous observations, here the susceptibility measurements did not reveal any anomaly in the vicinity of the resistive transition onset.